Single cell transcriptomics reveals the cellular heterogeneity of keloids and the mechanism of their aggressiveness - Xinwei Cheng; Zhen Gao; Shengzhou Shan; Haoyu Shen; Hongkun Zheng; Lu Jin; Qingfeng Li; Jia Zhou (Communications Biology)
Abstract Keloid is a dermatofibrotic disease known for its aggressive nature and characterized by pathological scarring, which often leads to disfigurement and frequent recurrences. Effective therapies for keloids are still limited, presumably due to the inadequate comprehension of their aggressive mechanisms. In our study, we examined the unique scenario where both keloid and non-aggressive pathological scar originate from the same patient, providing a rare opportunity to explore the aggressive mechanisms of keloids through single-cell RNA sequencing. We found that the dominant fibroblast subgroup in keloids is mechanoresponsive group, which showed enhanced mechanotransduction and migration. This mechanoresponsive fibroblast subgroup is likely to be the key cell population and confer aggressive growth of keloids. The results also indicate that the endothelial cells and keratinocytes in keloid involve in endothelial-mesenchymal and epithelial-mesenchymal transitions. This study demonstrated the mechanoresponsive fibroblasts and multiple cellular mesenchymal processes could pave the way for further investigations into the keloid aggressiveness.